Menerjemahkan Bahasa Arab: Antara Ilmu dan Seni - Siti Shalihah (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2017)
There are so many languages spoken by every community in the world today. This requires everyone to mastery various languages to facilitate the communication between members of one group to others. Because it would be a problem if members of one group communicate with one other member of the group but they do not understand each other, especially in the content of the message that delivered. Then we need translation to solve that issue. Translation is the process of transferring text messages of the source language into the target language. The practical purpose of the message diversion process is to assist the target language text reader in understanding the message intended by the original author of the source language text. This assignment assigns the translator to a very important position in disseminating science and technology. When science and technology are understood as part of a culture, indirect translators participate in the process of cultural transfer. Translating is not pure science and not pure art. Translating is a practical art. In other words, translating is the artistic skill with the help of theoretical sciences.